Policy Note for the Federalism Transition in Nepal - World Bank (World Bank, Washington, DC, 2020)
With the adoption of federalism through the 2015 Constitution, seven newly created provincial and 753 local governments are now placed at the frontline, tasked to manage substantial amount of public resources and deliver critical services to citizens. As result, Nepal is now in the middle of the transition to federalism, and it is understandable that the process will be a drawn-out one, which could take decades. This policy note has been prepared based on the findings, analyses and recommendations of the Federalism Capacity Needs Assessment (FCNA) study. The FCNA was conducted by the Georgia State University in 2018-2019 for the government of Nepal (GoN) with the joint support of the World Bank and UNDP. It has identified the gaps between the needs and the capacity in different levels of government. This note provides a synthesis of the FCNA findings as well as its forward-looking recommendations in terms of actions the government could take in the immediate, medium and long-terms towards a full realization of the benefits of federalism implementation in Nepal.